Biliary complications after liver transplantation. (April 2015) - Nemes, Balázs; Gámán, György; Doros, Attila
Abstract : Biliary complications (BCs) remain one of the most outstanding factors influencing long-term results after orthotopic liver transplantation. The authors carried out a systematic overview of 1720 papers since 2008, and focused on 45 relevant ones. Among 14, 411 transplanted patients the incidence of BCs was 23%. Biliary leakage occurred in 8.5%, biliary stricture in 14.7%, mortality rate was 1–3%. Risk factors: preoperative sodium level; p = 0.037, model of end-stage liver disease score >25; p = 0.048, primary sclerosing cholangitis; p = 0.001, malignancy; p = 0.026, donor age >60, macrovesicular graft steatosis; p = 0.001, duct-to-duct anastomosis; p = 0.004, long anhepatic phase; p = 0.04, cold ischemic time >12 h; p = 0.043, use of T-tube; p = 0.032, insufficient flush of bile ducts; p = 0.001, acute rejection; p = 0.003, cytomegalovirus infection; p = 0.004 and hepatic artery thrombosis; p = 0.001. The management was surgical in case of biliary leakage, and interventional radiology or endoscopic retrograde cholangiopancreatography in case of biliary stricture. Mapping of miRNA profile is a new field of research. Nemes–Doros score is a useful tool in the estimation of hepatic artery thrombosis. Management of BCs requires a multidisciplinary expert team.